The Effect of Language Barriers on Dispatching EMS Response. (1st October 2013) - Meischke, Hendrika W.; Calhoun, Rebecca E.; Yip, Mei-Po; Tu, Shin-Ping; Painter, Ian S.
Abstract: Objective. The objective of this study was to investigate the effect of language barriers during medical 9-1-1 calls, on the time to dispatch and level of medical aid (Basic or Advanced Life Support).Methods. All 9-1-1 medical calls to two large call centers during one week for each of the months of August, October, December 2010 and February 2011, were reviewed for a notation of language barrier (LB). Non-language barrier calls were identified from the same time period such that there were an equal proportion of LB and non-LB calls by dispatch code and dispatcher. A total of 272 language barrier calls were identified. The computer-assisted dispatch (CAD) reports for the LB and non-LB calls were abstracted by research staff using a standard form, including: Start time of call, time to dispatch of BLS, time to dispatch of ALS, dispatch code, interpretation service use, on-scene upgrade to ALS, and on-scene downgrade to BLS. 9-1-1 recordings were abstracted for LB calls only to obtain information about use of interpreter services. Difference between LB and English speakers in time to assignment of BLS and ALS was examined using linear mixed effects models with log time as the outcome; language barrier, call center and dispatch code as fixed effects and dispatcher as a random effect.Results. The effect of language barrier on time to BLS assignment was, on average, 33% longer ( p < 0.001) and time to ALS assignment 43% longer ( P = 0.008). A majority of the effect was due to the effect of interpreter use, which increased time to BLS by 82% and 125% for ALS, when compared to non-language barrier calls. Data from the 9-1-1 recordings showed an average of 49 seconds between connecting to the service operator and connecting to the language interpreter. Language barrier calls were more likely to be up- and down-graded, only statistically significantly so for on-scene downgrades.Conclusion. Language barriers increase time to dispatch and the accuracy of the level of aid dispatched during medical emergency calls. Decreasing the time to connecting to an actual interpreter when using an interpretation service could minimize existing delays.